Developing a Research Agenda Aimed at Understanding the Teaching and Learning of Science at a Natural History Museum. (October 2016) - Hammerness, Karen; MacPherson, Anna; Gupta, Preeti
Abstract: Over the past two decades, cultural institutions such as museums are beginning to develop their capacity for engaging in long‐term research on teaching and learning (Rennie et al. 2003; see also Crowley 2014). In this article, we describe one museum's efforts to develop an educational research agenda in relationship to these broader efforts. We explain how we got started; share steps taken; describe the agenda itself; and give examples of some of our current research studies. We end with insights into some of the challenges we've faced in developing this work and how we've addressed them and our next steps.